Gokhale : the Indian moderates and the British Raj - Nanda, B. R. (Bal Ram), 1917-2010. (Delhi ; Oxford : Oxford University Press, 1998)
A biography of Gokhale, one of the pre-eminent leaders of India during its struggle for freedom from colonization, which reassesses the Indian political scene during the last decades of the 19th century and the first decade of the 20th century.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gokhale, Gopal Krishna, -- 1866-1915.; Statesmen -- India -- Biography; India -- Politics and government -- 1857-1919.